Adolescent Delinquency and the Crime of Robbery in the Study of Criminal Theory - Rohmat, Rohmat; Ashtaputre, Shrirang; Smith, Robert Brian (IJCLS (Indonesian Journal of Criminal Law Studies), 2022)
No one wants a crime to occur in their community, because the existence of this crime will be disturbing and detrimental to people's lives. Therefore, crime must be tackled and stopped. This article discusses cases of adolescent delinquency, burglary crimes and labeling practices in the study of criminological theories. It is important to understand cases of adolescent delinquency, crime of robbery and labeling practices in terms of the characteristics of crime and criminals. The research method used is a normative juridical research method with secondary data sources. The results showed that there were 5 (five) theories that could be used to analyze adolescent delinquency cases, namely the French sect, differential association, anomie, social control, and learning theory. While the crime of robbery is analyzed in 4 (four) theories, namely classical criminology theory, positive criminology, differential association, and opportunity theory. Meanwhile, the case of labeling in society was studied using labeling theory. The above theories can be used as a strategy to prevent and prosecute juvenile crimes, in this case juvenile brawls as a special crime, burglary crimes, and community labeling practices. It can be concluded that increasing family participation as the first medium of learning for children by increasing control, so that brawls between teenagers can be anticipated, as well as increasing community participation and social control as well as preventive, curative, and repressive actions to prevent actions that violate social norms and legal norms.